The Clinical Course of Rheumatoid Arthritis in Kazakhstani Patients - Issilbayeva, Argul; Meiramova, Assel; Kushugulova, Almagul R.; Akhmetova, Zhanar B.; Biktashev, Damir; Abdakhina, Baglan B.; Aituganova, Aliya T.; Zueva, Yekaterina; Karlygash, Karina; Ainabekova, Bayan A. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Rheumatoid arthritis (RA) prevalence according to the worldwide epidemiological data varies from 0.4% to 1.3%. The disability and mortality rate in RA is high. RA clinic is various, and compiles from articular and systemic manifestations. AIM: The aim of our study was to investigate the clinical course of RA in Kazakhstani patients living in North region of our country. METHODS: The 81 women at the age of 30–55 years with a verified diagnosis of RA who have lived in Kazakhstan for at least 10 years were recruited to the study. All participants were examined by the rheumatologist and a standard laboratory examination was carried out. Statistical analysis was conducted in IBM SPSS Statistics 26 software (IBM.USA;1). RESULTS: The statistically significant higher frequency of erosive radiological stages, bone ankylosis (χ2 = 18.070 df = 6 p = 0.005) was found in seropositive (rheumatoid factor [RF]+) anti-citrullinated protein/peptide antibody positive (ACPA+) subgroup. The correlation analysis showed strong association between certain RA form activity and inflammatory markers, as well as disease triggers. The discriminant model which predicts the stage of radiological damage was obtained. The sensitivity of model in predicting X-ray Stage I-71.6%, Stage II-29.4%, Stage III-37.5%, and Stage IV-63.6%. CONCLUSION: The debut of the RA on average occurred in the third decade of the patients’ life. The joint syndrome had a more unfavorable character RF+ACPA+ patients’ subgroup; however, RF+ACPA-negative (ACPA-) subgroup also showed a predisposition to poorer prognosis. The obtained discriminant model may be useful for RA patients’ management.